Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula - López de Heredia, U.; Carrión, J. S.; JIMÉNEZ, P.; COLLADA, C.; Gil, L. (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.
Keywords: cpDNA PCR-RFLPs; evergreen Quercus; fossil pollen; glacial refugia; iberian peninsula; introgression; nested clade analysis; oaks; phylogeography